The impact of climate change on the symbiosis between dark septate endophytic fungi and rice plant - Mai, Ei Ngwe Zin (2020)
The purpose of this research is to clarify the symbiotic features of endophytic fungi in the early stage of rice growth and to evaluate the impact of high temperature on rice-endophytic symbiosis through the observation of the fungi present in the roots. The symbiosis activity between the dark septate endophytes (DSE) and Koshihikari rice plant under high temperature was tested by comparing morphophysiology of rice colonize with Cladophialophora chaetospira (OGR3), Meliniomyces variabilis (J1PC1), Phialocephala fortinii (LtPE2), Veronaeopsis simplex (Y34) and without colonization under continuous high temperature of 35°C. Root colonization was investigated under the microscope and the plant growth parameters such as root/shoot ratio, shoot high, etc., were measured. The colonization capacity of DSE fungi in the roots of the rice plant was demonstrated for all the selected species at 35ºC. The research will provide fundamental scientific background of endophytic fungi application for global warming application in agriculture.